2020
DOI: 10.1111/luts.12355
|View full text |Cite
|
Sign up to set email alerts
|

Is medicinal ketamine associated with urinary dysfunction issues? Assessment of both the European Medicines Agency (EMA) and the UK Yellow Card Scheme pharmacovigilance database‐related reports

Abstract: Objective A range of ketamine‐induced uropathy (KIU) issues have been typically described in ketamine misusers. Conversely, more knowledge is needed in terms of medicinal ketamine‐related urological disturbances, since ketamine prescribing is being increasingly considered for a range of medical and psychopathological conditions. Methods To assess medicinal KIU issues, we aimed at analyzing both the 2005–2017 European Medicines Agency (EMA) and the 2006–2018 UK Yellow Card Scheme (YCS) pharmacovigilance databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…According to the European Medicines Agency (EMA) and the UK Yellow Card Scheme pharmacovigilance database about 23% and 17% of ketamine-related adverse drug reactions (ADR) respectively referred to renal/urinary disorders. Interestingly, such issues being more common among women than men [94]. In general, urological problems occur within 1 month-1 year time frame following the start of ketamine use, but recent pharmacovigilance data revealed that even an acute ketamine administration may be associated with urological risks, as in some cases the risk was noticed within 48 hours of treatment [94].…”
Section: Ketamine-induced Uropathy: "The Ketamine Bladder"mentioning
confidence: 99%
See 1 more Smart Citation
“…According to the European Medicines Agency (EMA) and the UK Yellow Card Scheme pharmacovigilance database about 23% and 17% of ketamine-related adverse drug reactions (ADR) respectively referred to renal/urinary disorders. Interestingly, such issues being more common among women than men [94]. In general, urological problems occur within 1 month-1 year time frame following the start of ketamine use, but recent pharmacovigilance data revealed that even an acute ketamine administration may be associated with urological risks, as in some cases the risk was noticed within 48 hours of treatment [94].…”
Section: Ketamine-induced Uropathy: "The Ketamine Bladder"mentioning
confidence: 99%
“…Interestingly, such issues being more common among women than men [94]. In general, urological problems occur within 1 month-1 year time frame following the start of ketamine use, but recent pharmacovigilance data revealed that even an acute ketamine administration may be associated with urological risks, as in some cases the risk was noticed within 48 hours of treatment [94].…”
Section: Ketamine-induced Uropathy: "The Ketamine Bladder"mentioning
confidence: 99%
“…Reported bladder problems include: urinary cystitis caused by repeated dosing or long-term use; incontinence; painful bladder; bladder shrinkage; damage to the kidney and urethral obstruction, which can lead to the removal of the bladder; dilated common bile ducts and epigastric pain ( Bhattacharya, 2011 ; Colebunders and Van Erps, 2008 ; Ng et al., 2010 ; Wood et al, 2012a ). Some ketamine-related urinary dysfunction can occur after relatively short periods of use ( Schifano et al, 2020 ). Longer exposure to ketamine and depression appear to increase the risk of lower urinary tract symptoms ( Chen et al., 2018 ).…”
Section: ‘State-of-the-art’ Reviewmentioning
confidence: 99%
“…These molecules produce similar effects to LSD but possess a higher potency [10]. All these serotonergic agents may induce a serotonin syndrome, hepatic toxicity, and modifications of endocrinological function [22] (Table 1).…”
Section: Novel Stimulants: Synthetic Cathinones and Psychedelic Phene...mentioning
confidence: 99%
“…Subjective effects (e.g., 'K-hole') include dissociation from both the setting and the body, auditory/visual hallucinations, unusual thought content, euphoria and visual distortions [10]. Its related risks may include trauma, drowning, death from hypothermia, traffic accidents [5], and severe urinary dysfunction issues [22] (Table 1).…”
Section: Phencyclidine (Pcp)-like Substancesmentioning
confidence: 99%